PERANAN AUSTRALIA DALAM PEMBANGUNAN ACEH PASCA BENCANA TSUNAMI MELALUI KERANGKA KERJASAMA AIPRD (AUSTRALIA-INDONESIA PARTNERSHIP FOR RECONSTRUCTION AND DEVELOPMENT) PERIODE 2005-2009 - Wiswa Dhamana, A.A.Alit Maradi; Wiranata, I Made Anom; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRAK Nowadays,  development is one of the important aspects and have  been an international agenda. In 2004, Indonesia was hit by tsunami that caused damage to various aspects of life in Aceh, it certainly would hamper development in Indonesia. This disaster attracted sympathy from other countries to assist Indonesia in reconstruction  of Aceh post tsunami. One of them is Australia with its development agency AusAID (Australian Agency for International Development). AusAID as the Australian government development agencies that play roles in international development. AusAID as the Australian development agency has provided ODA (Official Development Assistance) bilaterally to Indonesia. The aid later formed a partnership AIPRD (Australia-Indonesia Partnership for Reconstruction and Development) aimed at the develop and reconstruction of Aceh after the disaster. This aid distributed to develop all sectors such as education, health, governance, livelihoods, housing and infrastructure. This study aims to describe the roles of Australia in the process of development and reconstruction of Aceh post tsunami through AIPRD program in the year 2005-2009. Keywords : Roles, development, development agency, foreign aid, AusAID, Aceh